2016
DOI: 10.1063/1.4954840
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants of chemical reactions from semiclassical transition state theory in full and one dimension

Abstract: Semiclassical Transition State Theory (SCTST), a method for calculating rate constants of chemical reactions, offers gains in computational efficiency relative to more accurate quantum scattering methods. In full-dimensional (FD) SCTST, reaction probabilities are calculated from third and fourth potential derivatives along all vibrational degrees of freedom. However, the computational cost of FD SCTST scales unfavorably with system size, which prohibits its application to larger systems. In this study, the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(109 citation statements)
references
References 108 publications
1
108
0
Order By: Relevance
“…One can also use Taylor series expansions around the stationary points to obtain an approximate instanton solution analytically. [23][24][25][26][27] These approaches also have the potential to break down when the instanton pathway exhibits strong corner-cutting behaviour and deviates significantly from the transition state.…”
Section: Introductionmentioning
confidence: 99%
“…One can also use Taylor series expansions around the stationary points to obtain an approximate instanton solution analytically. [23][24][25][26][27] These approaches also have the potential to break down when the instanton pathway exhibits strong corner-cutting behaviour and deviates significantly from the transition state.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use one-dimensional semiclassical transition state theory (1D SCTST) 36,54 to calculate the canonical rate constants, k(T), at high pressure limit. We showed in a previous study 21 that our method is also applicable to the calculation of the microcanonical rate constant, k(E).…”
Section: One-dimensional Semiclassical Transition State Theorymentioning
confidence: 99%
“…To obtain the values of f 3 and f 4 , one can perform numerical differentiation using either the Hessian matrix elements at 2 displaced geometries or single point energies at 4 displaced geometries. In previous studies, 21,22,36 the Richardson extrapolation [59][60][61] was used to improve the accuracy of the numerical derivatives. However, as our recent study of the reactions with simulant molecules 22 showed that these reactions are strongly asymmetric, it is possible that the Richardson extrapolation fails to produce the correct derivatives.…”
Section: One-dimensional Semiclassical Transition State Theorymentioning
confidence: 99%
See 2 more Smart Citations